The Effect Of Wom And Advertising On Purchase Intention With Brand Awareness As Mediating Variable At Five Star Restaurants In Nusa Dua - Sri Wardani; Putu Utama; Irene H Sihombing (Publikasi Indonesia, 2021)
Five-star hotel restaurants in the Nusa Dua area managed by international chains have similarities, namely not achieved the restaurant sales targets set by the company, restaurants not being remembered and known by consumers, restaurants not being advertised in various media, and TripAdvisor rankings, bubble ratings, and reviews are low. The above phenomena are related to the theory of word-of-mouth communication, advertising, brand awareness, and purchase intention. Research is conducted on the effect of word-of-mouth communication and advertising on purchase intention with brand awareness as a mediating variable. This type of research is explanatory research with non-probability purposive sampling technique with data collection techniques through questionnaires. Questionnaires were distributed to customers who had stayed and visited Eight Degrees South Conrad Bali and The Shore Hilton Bali for a period of one month from July 2021 to August 2021. The respondents who answered the questionnaire were 170 respondents. SEM PLS analysis was used to analyze the data. This study found that brand awareness has a positive and significant effect on purchase intention. WOM and advertising have no significant effect on purchase intention. WOM and advertising have a positive and significant effect on brand awareness. Brand awareness significantly mediates WOM and advertising on purchase intention. Restaurant managers are advised to advertise hotel restaurants on social media and advertorial advertisements to build brand awareness and consumer purchase intentions. Future research to explore the possibility of being developed in the room and spa division.